2020
DOI: 10.1186/s12885-020-07306-1
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin(d35:1) as a novel predictor for lung adenocarcinoma recurrence after a radical surgery: a case-control study

Abstract: Background: To improve the postoperative prognosis of patients with lung cancer, predicting the recurrence highrisk patients is needed for the efficient application of adjuvant chemotherapy. However, predicting lung cancer recurrence after a radical surgery is difficult even with conventional histopathological prognostic factors, thereby a novel predictor should be identified. As lipid metabolism alterations are known to contribute to cancer progression, we hypothesized that lung adenocarcinomas with high recu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…Fourth, high SM synthase expression and aberrant SM contents were associated with breast cancer progression and metastasis [ 60 ]. Fifth, increased SM content in frozen tissue samples of primary lung adenocarcinoma obtained from patients who underwent radical surgery was the most reliable indicator of recurrence, i.e., of degree of malignancy [ 61 ]. Six, low levels of surface membrane-associated neutral sphingomyelinase (nSMase)-2, responsible for SM hydrolysis, were associated with early recurrence of hepatic cell carcinoma after surgery [ 62 ].…”
Section: Tumor Immune Evasionmentioning
confidence: 99%
“…Fourth, high SM synthase expression and aberrant SM contents were associated with breast cancer progression and metastasis [ 60 ]. Fifth, increased SM content in frozen tissue samples of primary lung adenocarcinoma obtained from patients who underwent radical surgery was the most reliable indicator of recurrence, i.e., of degree of malignancy [ 61 ]. Six, low levels of surface membrane-associated neutral sphingomyelinase (nSMase)-2, responsible for SM hydrolysis, were associated with early recurrence of hepatic cell carcinoma after surgery [ 62 ].…”
Section: Tumor Immune Evasionmentioning
confidence: 99%
“…Lipid extraction was performed as reported previously [ 18 ]. Briefly, we measured each tissue weight using a Sartorius analytical lab balance CPA224S (Sartorius AG, Göttingen, Germany) (Additional file 1 , Supplemental Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Survival under oxidative stress and energy stress are promoted by membrane saturation and lipid droplet formation, respectively [ 14 , 15 ]. Furthermore, some lipids have been suggested as prognostic factors in several cancer types [ 16 18 ]. In our previous study, increased sphingomyelin (SM)(d35:1) in lung adenocarcinoma (ADC) demonstrated excellent recurrence prediction ability (superior to histopathological factors) and was considered as a promising candidate predictor for recurrence after radical surgery [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations